Assessing the potential environmental impacts of hydropower projects in Myanmar: comparison with lignite thermal project and opportunity for clean development mechanism - Khin Seint Wint; Perret, Sylvain Roger; Babel, Mukand Singh; Shrestha, Sangam; Bohez, Erik L.J.; Electricity Generating Authority of Thailand (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
Hydropower as a source of renewable energy has drawn tremendous interest and investments in recent times in South East Asia, as the region is ill-endowed with fossil energy resources. Along with Southern China, Laos and Thailand, Myanmar has engaged into the development of reservoir projects, while more traditional energy generation techniques still apply (mostly coal-based). However, hydropower projects are raising concerns about their social and environmental impacts, the latter being largely unknown. Required Environmental Impact Assessments are not always carried out properly, and, in any case, fail to reveal possible regional or global impacts, nor transfers of impacts. The present study investigates the potential environmental impacts of two hydropower projects in Myanmar, as compared to one lignite thermal project, using the Life Cycle Assessment (LCA) approach. Further, it investigates the possibilities of implementing Clean Development Mechanism (CDM) scheme options for seeking financial support. The main case study is the so-called Upper Keng Tawng reservoir project, where initial environmental examination is finished, and yet EIA was not completed effectively. It was therefore proposed to undertake environmental impact analysis through LCA, as part of the research. The action does not mean a replacement of EIA, but it intends to provide a more complete picture of impact assessment including regional and global perspectives. LCAs of downstream run-of-river project and neighboring lignite thermal project (Tigyit) have also been carried out, to compare with that of the reservoir project. Static and attributional LCA, based on functional unit of 1 kWh, was performed. The approach considered materials, energy, land use, emission to air, water, and disposal/waste management during construction, and 50-year operation of the studied projects. Transmission and distribution of electricity are excluded from analysis. The SimaPro software (version 7.3) was used, using both EI-99 (H, A) and CML baseline methods for impact assessment. Adjustments from existing database proved necessary since the quality of lignite at Tigyit mine is higher than that of European lignite (667 g/kWh in Tigyit, 1,544 g/kWh in Slovakia, 1,979 g/kWh in Greece and 771 g/kWh in France). Considering 1 kWh of electricity generation at Tigyit coal thermal plant, total estimated impact is 154 mPt whereas impacts of European lignite thermal plants are situated in the range of (+ 15 %) to (- 68 %) of it. Compared with European LCIAs, LCIA of Tigyit coal thermal plant has been more thoroughly documented. It is found that 71 % of overall impact occurs due to particulate matters, sulphur dioxide and sulphur trioxide emission which causes troubles to human respiratory system. When many processes which are not considered in European LCIAs are discarded from the study, 1 kWh of electricity generation at Tigyit coal thermal plant contributes 86.7 mPt whereas impacts of European lignite thermal plants are situated in the range of (+104 % ) to (- 42 %) of it. The study displays that electricity generation of Upper Keng Tawng reservoir project causes 3.15 mPt per kWh and that of Keng Tawng run-of-river project makes 0.911 mPt per kWh. Potential impacts of Upper Keng Tawng reservoir project is 75 % higher than that of Keng Tawng run-of-river project. Compared with run-of-river projects in EU and Switzerland, Keng Tawng (Myanmar) contributes 11 % more impacts. Upper Keng Tawng reservoir project (Myanmar) makes 26 % more impacts than Brazilian reservoir projects. When impact contributions of Tigyit coal thermal project and Keng Tawng and Upper Keng Tawng hydropower projects are compared, reservoir project and run-of-river project
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Water Engineering and Management
Thesis (M.Eng.) - Asian Institute of Technology, 2011
Keywords: Cumulative effects assessment (Environmental assessment) -- Myanmar; Environmental impact analysis -- Myanmar; Water-power -- Myanmar